PEMETAAN SEBARAN DAYA TARIK WISATA DI DESA BULO SEBAGAI KAWASAN AGROWISATA KAB POLEWALI MANDAR SULAWESI BARAT - Muh Kasim; Muh Yahya; Masri Ridwan (JAMBURA GEO EDUCATION JOURNAL, 2022)
The purpose of this study was to map the distribution of tourist attractions in the agro-tourism area of Bulo Village, Bulo District, Polewali Mandar Regency. After careful scrutiny, it turns out that Bulo Agrotourism has entered as a leading tourist attraction in Polewali Mandar Regency. The research was conducted through a field survey using Garmin GPS to determine the location of tourist objects and area boundaries, data processing was carried out using ArcGIS 10.8. The data processing produces attribute data in the form of spatial and coordinate data, so that 6 (six) objects can be mapped including Anugerah Bulo Hill, Tapenangi Durian Garden, Bulo Botanical Garden, Lemo Nipi Hill, Uhai Sibali Peak and Senayan Hill. Meanwhile, based on the 3 (three) components of tourism which include Attractions, Accessibility and tourist activities that really need to be addressed are the accessibility components, including transportation service facilities so that tourists can visit agro-tourism at any time and feel comfortable and safe, because the road conditions to the location are still in pioneering, so that the policy makers should immediately fix the road facilities to each tourist attraction..